Experimental investigations on the liquid thermal conductivity of five saturated fatty acid methyl esters components of biodiesel. (October 2018) - Fan, Jing; Liu, Qi; Song, Fenhong; Wang, Xiaopo; Zhang, Lihui
Highlights: The thermal conductivity of five fatty acid methyl esters was measured. The experimental results of these methyl esters are reported for the first time. Based on the experimental data, a fitting correlation of temperature was proposed. Abstract: The utilization of biodiesel is a promising way to replace fossil fuels, and thermal conductivity of biodiesel is a very important thermophysical property for its applications. In this work, the transient hot-wire instrument with one bare platinum wire was used to measure the thermal conductivity of five pure components of biodiesel in liquid phase at atmospheric pressure. The measured substances include methyl butyrate, methyl pentanoate, methyl caproate, methyl caprylate, and methyl pelargonate, and the temperature range was from (283 to 358) K, (285 to 362) K, (263 to 368) K, (273 to 393) K, (278 to 383) K, respectively. The total standard uncertainty of the experimental results was estimated to be less than 2% and the repeatability was better than ±0.5%. The thermal conductivity data of each substance were fitted as a function of temperature. The average absolute relative deviation and maximum absolute relative deviation between the experimental data and calculated results were 0.17% and 0.44% for methyl butyrate, 0.25% and 0.58% for methyl pentanoate, 0.16% and 0.44% for methyl caproate, 0.15% and 0.47% for methyl caprylate, 0.15% and 0.33% for methyl pelargonate, respectively.